Pengaruh Kualitas Konten Pemasaran Di Tiktok Dan Tingkat Keterlibatan Terhadap Keputusan Pembelian Parfum Cruseka - Della Amanda Safira Putri; Asmirin Noor; Parwita Setya Wardhani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the influence of content quality and engagement level on consumer purchasing decisions for Cruseka perfume products through the TikTok platform. This study uses a quantitative method with data collection techniques through questionnaires distributed to 98 respondents online, specifically followers of the Cruseka perfume TikTok account based on certain criteria. The data is analyzed using multiple linear regression methods to determine the relationship between independent and dependent variables. The results show that content quality and engagement level have a simultaneous effect on purchasing decisions, which can significantly improve in this study. This explains that the content quality variable (X1) and the engagement level variable (X2) are functioning well, thus providing a positive impact.